Thin Layer Drying Kinetics Modelling of Curry Leaves (Murraya koenigii L.) in Cabinet Dryer - Ghimire, Arjun; Magar, Nirajan (Himalayan Journal of Science and Technology, 2018)
Curry leaves (Murraya koenigii L.) are the sweet smelling leaves of small tree of Rutaceae family native to Southwest Asia. In this study, the effect of temperatures (50, 55 and 60°C) on the drying of curry leaves was investigated. The experimental data were fitted to six thin layer mathematical models (Newton, Page, Handerson and Pabis, logarithmic, two-term exponential and Midilli et al). The models were evaluated in terms of coefficient of determination (R2), chi square (χ2) and root mean square error (RMSE). The Midilli et al model was best fitted to the experimental data of all the models evaluated. The effective diffusivity was calculated using Fick's diffusion equation, and the value varied from 2.07×10-12 m2/s to 2.643×10-12 m2/s. The activation energy and the diffusivity constant were found to be 21.808 kJ/mol and 4.667×10-8 m2/s respectively.